Measuring The Amount Of Consumer Desire During Live Streaming Shopping Of Cosmetic Products - Christiarini, Renny; Tarekar, Wendy Wihue; Purwianti, Lily (SKeTsa Bisnis (e-jurnal), 2025)
streaming shopping in the context of social commerce, specifically for cosmetic products followed by generation Z. The main focus of this research is to understand how generation Z interacts with live streaming shopping content and what factors influence their purchasing decisions. The main focus of this research is to understand how Generation Z interacts with live streaming shopping content and what factors influence their purchasing decisions. Methods, the research method used was to distribute questionnaires to 431 people from generation Z in Batam city who actively follow live streaming shopping for cosmetic products and using the Partial Least Square (PLS) method with Structural Equation Modelling (SEM) technique to process the collected data. Results, the results showed that eWOM, brand image, product, and promotion have a significant role in influencing generation Z's purchasing decisions. Conclusion, this research provides valuable insights for cosmetics industry players and social commerce platforms to design marketing strategies that are more effective and in accordance with generation Z's preferences.